Acoustic radiation characteristics of cutoff modes from ducts. (22nd December 2022) - Baddour, B.; Joseph, P.; McAlpine, A.; Leung, R.
Abstract: The acoustic radiation from a source inside a hard-walled semi-infinite duct or tube, such as for ducted fans and rotors, is investigated. In particular a study of cutoff modes, which have the potential to affect the far-field pressure radiation for sources close to the duct open end, is presented. A large amount of work has been done to mathematically and experimentally investigate propagating cuton acoustic modes. However, there is very little published work on the radiation of cutoff modes. This paper concerns the radiation characteristics of cutoff modes to determine their behaviour, and their likely influence in the far-field directivity for sources close to the duct open end. It is shown that cutoff modes are an essential contributor for the radiation in the rear-arc. Highlights: Cutoff modes radiate most strongly to the rear-arc. Cutoff modes exhibits directivities which are determined only by azimuthal order. The equivalent radiation velocity for cutoff modes is located beyond the sonic radius. The directivity of cutoff modes is symmetric about 90 ° at low frequency. The radiation efficiency of cutoff modes decreases sharply with azimuthal order.